Gamification in Islamic Religious Education Learning: Efforts to Increase Student Enthusiasm and Understanding - Nur Wahyuni (Al-Ilmu, 2026)
This study aims to analyze the implementation of gamification in Islamic Religious Education (PAI) learning to increase student enthusiasm and understanding in the digital era. The research method uses a qualitative approach with a comparative case study design conducted at MA Negeri 1 Purwokerto and MA Al-Ikhsan Purwokerto for 8 months. The research subjects included madrasah principals, PAI teachers, students from various grade levels, and parents of students selected through purposive sampling. Data collection techniques used triangulation including participant observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman interactive analysis model. The results show that gamification has succeeded in significantly increasing student enthusiasm for learning through the implementation of a point system, digital badges, leaderboards, and learning quests. The increase in active participation reached 78% at MA Negeri 1 and 72% at MA Al-Ikhsan, while understanding of PAI material increased by 68% and 62% at each madrasah. Supporting factors for success include school policy support, teacher technological competence, adequate infrastructure, and student enthusiasm for learning innovations. The main obstacles are limited technological devices and the need for intensive training for teachers. Gamification has proven effective in creating interactive, enjoyable, and meaningful Islamic Religious Education (PAI) learning while maintaining the substance of Islamic values. The research recommends developing contextual gamification models, continuously improving teacher competency, and providing technological infrastructure to optimize digital-based PAI learning.